Development of computer assisted cost model for activity based management in a manufacturing company [electronic resource] - Asyraff Abdullah, 1985- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - industri)) - Universiti Teknologi Malaysia, 2008